2022
DOI: 10.1002/ange.202204262
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Metalating Efficiency of the Sodium Amide NaTMP in Arene Borylation Applications

Abstract: Though LiTMP (TMP=2,2′,6,6′‐tetramethylpiperidide) is a commonly used amide, surprisingly the heavier NaTMP has hardly been utilised. Here, by mixing NaTMP with tridentate donor PMDETA (N,N,N′,N′′,N′′‐pentamethyldiethylenetriamine), we provide structural, and mechanistic insights into the sodiation of non‐activated arenes (e.g. anisole and benzene). While these reactions are low yielding, adding B(OiPr)3 has a profound effect, not only by intercepting the CAr‐Na bond, but also by driving the metalation reactio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 64 publications
(16 reference statements)
0
4
0
Order By: Relevance
“…Despite all these advances, the detailed study of the reaction mechanism is still lacking in some of these transformations. DFT calculations and key mechanistic experiments have been performed in a few examples, 13,16,18,21,23,27,28,30 but in general the specific mechanistic details of these processes are still poorly understood. We predict that further developments on the use of alkali-metal bases for HIE processes will keep appearing, which in combination with a deeper mechanistic understanding will bring the use of alkali-metal bases as an excellent pathway for the incorporation of deuterium and tritium into organic molecules, with the benefits of using widely available and cheap alkali-metal reagents.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Despite all these advances, the detailed study of the reaction mechanism is still lacking in some of these transformations. DFT calculations and key mechanistic experiments have been performed in a few examples, 13,16,18,21,23,27,28,30 but in general the specific mechanistic details of these processes are still poorly understood. We predict that further developments on the use of alkali-metal bases for HIE processes will keep appearing, which in combination with a deeper mechanistic understanding will bring the use of alkali-metal bases as an excellent pathway for the incorporation of deuterium and tritium into organic molecules, with the benefits of using widely available and cheap alkali-metal reagents.…”
Section: Discussionmentioning
confidence: 99%
“…Mechanistic investigations revealed that under stoichiometric conditions using C 6 H 6 or hexane as a solvent the starting materials are in equilibrium with the relevant sodium aryl and the amine TMP(H). 27 Further evidence on the metalating ability of NaTMP to deprotonate anisole and benzene was obtained by the isolation and structural identification of the organometallic species involved in these reactions (Fig. 8b) which can be envisaged as co-complexes between the metalation products NaAr (Ar = C 6 H 4 –OMe, C 6 H 5 ) and the sodium amide NaTMP·L (L = TMEDA, N , N , N ′, N ′-tetramethylethylenediamine).…”
Section: Hydrogen Isotope Exchange With Alkali-metal Basesmentioning
confidence: 99%
See 2 more Smart Citations
“…However, these reagents are highly reactive and tend to attack electrophilic DMGs or sensitive functional groups, causing undesired side reactions . Subsequent research to establish alternative, less harsh metalation reagents has been fruitful, with the discovery of metalation reagents in the form of single metals (Na), sodium and metal amides, , sodium isopropyl­(trimethylsilyl)­amide, NaTMP (TMP = 2,2′,6,6′-tetramethylpiperidine) with tridentate donor PMDTA ( N , N , N ′, N ″, N ″-pentamethyldiethylenetriamine), mixed metals, , metalates (magnesiates, zincates, and aluminates), (2,2,6,6-tetramethylpiperidino)magnesium chloride (TMPMgCl), mixed aggregates, , “superbases,” and “Turbo bases”. , There are only a few examples which have been demonstrated for ArOAms, shown in Table .…”
Section: Directed Ortho Metalation (Dom) Chemistrymentioning
confidence: 99%